Complementary theraphy as an approach in managing occupational stress - Nur Aishah, Binti Nor Hashim (Universiti Malaysia Sarawak (UNIMAS), 2015)
Occupational stress is caused by various reasons such as workload and long working hours. Thus, numerous Occupational Safety and Health practitioner have showed a concern towards occupational stress issue and started on promoting mental health awareness at workplace. Meanwhile, there is an occurrence of trend in using wellness activities to treat physical and psychological illness which is known as complementary therapy. It is a type of treatment which can also be described as a non conventional medicine. Some of the examples are Yoga, Aromatherapy, Qi gong, and Islamic Medical Practices (Ruqyah). Therefore, this research offered a perspective on the use of complementary therapies as a tool in improving and maintaining mental health condition of employees. 5 complementary therapy practitioners were interviewed and distributed with questionnaires for this study to satisfy the research objectives on identifying the perceptions towards the use of complementary therapy, to identify what are the type of therapy that can be practiced to reduce stress and how do the therapies affect occupational stress. It is found that complementary therapy is very beneficial as it act as a holistic treatment, natural way of healing and more empowering as it helps to improve employee's mental, emotional and physical health.